Social Dynamics of the Families of Former Online Gamblers: Narrative Study of Former Online Gamblers in Wonomulyo District, Sidodadi Village, Polewali Mandar Regency - Alalwi, Ahmad Gazali; Kaharuddin, Kaharuddin; Jamaluddin, Jamaluddin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to determine 1) Changes in social functions within a family after one of its members stops being an online gambler, and 2) The meaning of the status of "former online gambler" is constructed by family members and the social environment. This study uses a qualitative descriptive method. The technique in determining informants uses purposive sampling. The number of informants is 5 people. The data collection techniques used are observation, interviews, and documentation. The data validation technique uses member check. The data analysis techniques are data reduction, data presentation, and drawing conclusions. The results of the study show that: 1) Changes in social functions within a family after one of its members stops being an online gambler, namely: the involvement of family members in online gambling causes disruptions in the function of affection, economy, and social roles in the household. After the perpetrator stops gambling, the family goes through a process of recovery and adaptation. 2) The meaning of the status of "former online gambler" is constructed by family members and the social environment, namely: success in restoring family functions. However, in the formation of a new social identity in the environment has not been fully recovered, because it is influenced by emotional support, positive symbolic interactions, and the perpetrator's consistency in showing real changes in the surrounding environment.